2010
DOI: 10.1159/000321694
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Small-for-Gestation Neonates from Biophysical and Biochemical Markers at 11–13 Weeks

Abstract: Objective: To develop a model for prediction of small-for-gestational age (SGA) neonates in the absence of preeclampsia (PE) based on maternal factors and biophysical and biochemical markers at 11–13 weeks’ gestation. Methods: Screening study in 1,536 SGA and 31,314 non-SGA pregnancies based on maternal characteristics, fetal nuchal translucency (NT) thickness, serum pregnancy-associated plasma protein-A (PAPP-A) and free β-human chorionic gonadotrophin (β-hCG). We also measured mean arterial pressure (MAP), u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
171
2
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 174 publications
(189 citation statements)
references
References 48 publications
12
171
2
4
Order By: Relevance
“…[Sch] [9,12,[15][16][17][18] Of the 8 studies, only 4 reported raw PP13 concentrations in controls for assessment of normative levels in first trimester of pregnancy, [Sch] [16,17,19] and these were presented in various formats.…”
Section: Systematic Review and Meta-analysismentioning
confidence: 99%
See 4 more Smart Citations
“…[Sch] [9,12,[15][16][17][18] Of the 8 studies, only 4 reported raw PP13 concentrations in controls for assessment of normative levels in first trimester of pregnancy, [Sch] [16,17,19] and these were presented in various formats.…”
Section: Systematic Review and Meta-analysismentioning
confidence: 99%
“…[17] In comparison, median level of PP13 among controls in the in-house study was 53.5 (IQR; 37.7-71.8) pg/ml for all woman, 54.7 (IQR; 39.8-72.1) pg/ml for nulliparous women and 53.9, 54.0, 52.5 pg/ml for gestational week 11-13, respectively. [Sch] Although, a number of the studies found a significant difference in PP13 MoM levels between cases and controls for preeclampsia, [Sch] [12] early-onset preeclampsia [12,15,16] and SGA; [Sch] [9] three studies found no association between PP13 levels and adverse pregnancy outcomes. [9,17,18] In most studies, diagnostic accuracy of each outcome was determined at fixed cut-points of false positive rates of 5%, 10% and 20%.…”
Section: Systematic Review and Meta-analysismentioning
confidence: 99%
See 3 more Smart Citations